Analisis Pengaruh Product Quality, Discount & Interactivity terhadap Repurchase Intention melalui Customer Satisfaction pada Live Streaming Shopping - Syarifah Nada Fauzana; Hairudinor (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: The purpose of this study is to test and determine the direct and indirect influence between Product Quality, Discount & Interactivity on Repurchase Intention through Customer Satisfaction on Live Streaming Shopping. This study uses quantitative research methods with an explanatory type and uses the SmartPLS data analysis method by collecting data through distributing questionnaires to Indonesian people who have shopped via live streaming platforms with a sample of 113 respondents. The results of this test prove that Product Quality has a significant effect on Customer Satisfaction. Discounts have a significant effect on Customer Satisfaction. Interactivity has a significant effect on Customer Satisfaction. Product Quality has no significant effect on Repurchase Intention. Interactivity has no significant effect on Customer Satisfaction. Customer Satisfaction has a significant effect on Repurchase Intention. And Product Quality, Discount & Interactivity have an indirect effect on Repurchase Intention through Customer Satisfaction